THE LOST ANCESTOR OF THE BROAD BEAN (VICIA FABA L.) AND THE ORIGIN OF PLANT CULTIVATION IN THE NEAR EAST - O. E. Kosterin (Вавиловский журнал генетики и селекции, 2015)
The broad bean (Vicia faba L.) was among the founder crops of the Near East; nevertheless, its wild close relatives remain unknown. Presumably, its missing wild progenitor had a small range within the Levant and was associated with restricted habitats, so that it was domesticated entirely as a species. Its habitats are supposed to have been situated along floodplain/slope borders (“transeluvial-accumulative barriers”) providing favorable edaphic conditions. These restricted natural habitats of the broad bean could be foci of early cultivation activities, thus becoming nascent fields. It is hypothesized that the broad bean, a conspicuous plant with large seeds and restricted habitats, could be the Near Eastern “primer crop”, which provoked the first emergence of the idea and practice of plant cultivation and “invention” of the field.